Reconstruction of a county-level resolution typhoon disaster database from 1980 to 2018 for China’s coastal area - Wu, Caiming; Ren, Fumin; Zhu, Jing; Chen, Peiyan; Lu, Yi (Frontiers in Earth Science, 2023)
This study develops a reconstructed typhoon disaster database over a longer period 1980–2018 and at higher spatial resolution by using the county-level resolution disaster records for the eight coastal provinces of China during the shorter period 2004–2013. Typhoon precipitation and wind data over the shorter period are matched to disaster data and a functional relationship is derived between typhoon meteorological impact and typhoon disaster (direct economic loss). This relationship is used to construct a disaster data set for a longer period. The basic characteristics of the reconstructed database are documented and analyzed. The above analyses show that, firstly, the reconstructed disaster data are consistent with the recorded data due to the highly significant correlation. Secondly, an appropriate reconstruction method is developed, involving three main phases: disaster data expansion for individual stations, establishment of relationships between disaster and typhoon precipitation and wind, and disaster database reconstruction. Thirdly, the annual cumulative damage shows an insignificant downward trend over time. Typhoon damage mainly occurred between July and September each year. Landfalling typhoons that moved northwestward and then turned northward always caused more severe damage in China. In general, the reconstructed disaster database can provides a data basis to typhoon risk and disaster mechanism researches.